Utilisation of traditional medicine among women diagnosed with breast cancer in Ghana: a descriptive phenomenological study - Adwoa Bemah Boamah Mensah; Stella Baffour Asuo; Kofi Boamah Mensah; Joshua Okyere; Shalini Kulasingam; Beth Virnig; Joe-Nat Clegg-Lamptey (BMC Complementary Medicine and Therapies, 2024)
Abstract Background Women living with breast cancer (BC) rely on traditional medicine (TM) in addition to orthodox medicine. There is a need to understand how and why women diagnosed with BC utilise TM. This study explored and described the lived experiences of women living with BC in terms of their utilisation of traditional medicine. Methods A descriptive phenomenology design was used to purposively conduct 20 face-to-face in-depth interviews using a semi-structured interview guide. Data were analysed using NVivo-12 based on Collaizzi’s framework for thematic data analysis. Results Overall, five main themes emerged, namely: sources of knowledge on TM, motivations for using TM, treatment modalities, timing for the initiation of TM, the reasons for discontinuing use of TM, and the decision to seek orthodox medicine. Under the category of motivations for using TM, four themes emerged: financial difficulties and perceived cost effectiveness of TM, influence of social networks, including family and friends, assurance of non-invasive treatment, delays at the healthcare facility, and side effects of orthodox treatment. Non-invasive treatments included herbal concoctions, natural food consumption, and skin application treatments. Regarding the timing of initiation, TM was used in the initial stage of symptom recognition prior to the decision to seek orthodox medicine, and was also used complementarily or as an alternative after seeking orthodox medicine. However, patients eventually stopped using TM due to the persistence of symptoms and the progression of cancer to a more advanced stage, and disapproval by orthodox practitioners. Conclusion Women living with BC in Ghana utilise traditional medicine (TM) for many reasons and report their family, friends and the media as a main source of information. A combination of herbal concoctions and skin application modalities is obtained from TM practitioners to treat their BC. However, they eventually discontinue TM when symptoms persist or when disapproval is expressed by their orthodox healthcare providers. We conclude that there is an opportunity to better integrate TM into the standard of oncological care for BC patients.